Mecanismos de controle da evapotranspiração em um gradiente de ecossistemas tropicais em Mato Grosso - Pedreira Junior, Altemar Lopes (2021)
Mato Grosso presents a complex variability of distinct ecosystems that play a fundamental role in the terrestrial surface water transfer to the atmosphere, which stands out for the evapotranspiration process. The objective of the study was to evaluate evapotranspiration and the mechanisms that control it in a gradient of tropical ecosystems in Mato Grosso. The study was carried out in four experimental sites (Sinop, Fazenda Miranda, Baía das Pedras and Cambarazal), which are distributed in the North-South direction of the state. Field surveys were carried out by sensors installed in flow towers at each experimental site between 2003 and 2015. Data were obtained on monthly, annual and seasonal intervals. Actual evapotranspiration, crop coefficient, aerodynamic and canopy conductance on a monthly, annual and seasonal scale were higher in Cambarazal. Reference evapotranspiration on a monthly, annual and seasonal scale was higher in Baía das Pedras, except for the dry season when reference evapotranspiration was higher at Fazenda Miranda. The air temperature, global radiation and the Steam Pressure Deficit were the climatic variables that had the greatest influence and direct effect on evapotranspiration in all experimental sites. The decoupling factor on a monthly, annual and seasonal scale shows a similar behavior among all experimental sites, indicating that the control exercised by the availability of energy is greater during the rainy season. Physiological factors play a more important role during the dry season. Therefore, evapotranspiration showed consistent annual, seasonal and monthly variations. Thus, the hypothesis that there is a gradient of evapotranspiration in the state of Mato Grosso is true and is influenced by atmospheric and physiological variables.